Conference Reflection: Reflections on the '8th International Research and Development Seminar on Environmental and Health Education', South Africa, March 2005 - Maria Jose Hernandez Ramos (Environmental Association of Southern Africa, 2005)
The outlook of social research in general, and of environmental education research in particular, is uncertain; the existing plurality and contradictory nature of the epistemological, methodological and theoretical approaches paint a rather confusing picture for novice researchers. PhD candidates struggle with the challenge of undertaking quality research in a field where there is no clear agreement about what quality in research means. From this perspective, the 8th International Research and Development Seminar on Environmental and Health Education represented an invaluable experience for attending PhD candidates like me. I was one of a group of PhD students given the opportunity to present their 'work in progress' at the 8th International Research and Development Seminar. Any novice researcher can identify with how daunting a possibility it seems to share one's research concerns with the experts in the field, especially in the area of methodology. If, however, there are times when taking a risk pays off, this was certainly one of them. I can't say it was not a demanding experience; the feedback I received reflected the plurality of views that environmental education research can generate. On one hand there were contributions that complemented the framework of my research very well, and on the other hand there were those that threatened to plunge it into utter disarray. However, these conflicting views challenged my thinking and broadened my perspective, and more importantly, this environment of contestation enabled me to reaffirm my own perspective and views and thus position myself as a researcher. A plurality of approaches is part of the richness inherent in research. It does, however, present challenges, especially for novice researchers like me. As a research apprentice, core aspects of my knowledge and identity as a researcher are still under construction, and I must mediate between my capacity to be reflexive and my capacity to commit to positions I do not want to change. As a result of my attendance at the Research Seminar I have revised the main aspects of my research to incorporate some of the deliberated ideas. However, this seminar contributed greatly not only to my research progress but also to my capacity for defining, knowing and identifying myself as a researcher.